Postservice lower limb amputation in Scottish military veterans. Issue 1 (25th January 2021) - Bergman, Beverly P; Mackay, DF; Pell, JP
Abstract : Introduction: Recent attention has focused on veterans who have lost limbs in conflict, but the number of UK veterans who lose limbs to disease is unknown. We used data from the Trends in Scottish Veterans' Health study to explore postservice lower limb amputation. Methods: We carried out a retrospective cohort study of 78 000 veterans and 253 000 non-veterans born between 1945 and 1995, matched for age, sex and area of residence. We used survival analysis to examine the risk of amputation in veterans compared with non-veterans, and explored associations with antecedent disease. Results: We found no difference between veterans and non-veterans in the risk of lower limb amputation, which was recorded in 145 (0.19%) veterans and 464 (0.18%) non-veterans (Cox proportional hazard ratio (HR) 1.00, 95% CIs 0.82 to 1.20, p=0.961). Peripheral arterial disease was recorded in two-thirds of both veteran and non-veteran amputees, and type 2 diabetes in 41% of veterans and 33% of non-veterans, with a dual diagnosis in 32% of veterans and 26% of non-veterans. Trauma was an infrequent cause of amputation. Conclusions: Although in later life veterans are no more likely to lose a limb to disease than non-veterans, the number so affected greatly outweighs those who have lost limbs in conflict. The high public profile of conflict-related limb loss risks eclipsing the needs of veterans with disease-related loss. Support for ageing veterans who have lost limbs due to disease will require planning with the same care as that afforded to the victims of conflict if inequalities are to be avoided.